Oxford reading tree: floppy's phonics level 2. Book 9, zz, qu, ch - Hepplewhite, Debbie; Hunt, Roderick Brychta, Alex (Oxford University Press Oxford, 2011)
Level 2 Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 3 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.